PENGARUH KENAIKAN HARGA KOMODITAS SEMBAKO TERHADAP DAYA BELI KONSUMEN KELURAHAN PONDOK LABU KECAMATAN CILANDAK JAKARTA SELATAN - Zahro, Erlina Laila; Wahyuningsih, Sri; Anshori, Anshori (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
The problem in this study is the increase in basic food (sembako) prices that pressures the purchasing power of middle-to-lower-income households in Kelurahan Pondok Labu, South Jakarta. The purpose of this research is to analyze the effect of rising food commodity prices on consumer purchasing power. The study applied a quantitative approach with a survey method and simple linear regression analysis. Data were obtained from 58 housewives through questionnaires. The instruments were declared valid, reliable, and fulfilled classical assumption tests. The results show that the increase in sembako prices has a significant effect on consumer purchasing power (sig. 0.000 < 0.05; t-count 5.245 > t-table 1.673). Shallots were identified as the most affected commodity, followed by garlic, chili, and eggs. The discussion reveals that households respond by reducing purchase volumes, seeking cheaper alternatives, and adjusting their budgets to maintain economic stability.